Fielding vaccines-challenges and opportunities in outbreaks, complex emergencies, and mass gatherings - Laura J. Fischer; Robert C. Rains; Sherry M. Brett-Major; Mikiko Senga; Debra Holden; David M. Brett-Major (Taylor & Francis Group, 2022)
With the recent COVID-19 pandemic, the importance of vaccine development, distribution, and uptake has come to the forefront of the public eye. Effectively fielding vaccines during an emergency-whether that emergency is a result of an infectious disease or not-requires an understanding of usual vaccine-related processes; the impact of outbreak, complex emergencies, mass gatherings, and other events on patients, communities, and health systems; and ways in which diverse resources can be applied to successfully achieve needed vaccine uptake. In this review, both the emergency setting and briefly vaccine product design are discussed in these contexts in order to provide a concise source of general knowledge from experts in fielding vaccines that can aid in future vaccine ventures and increase general awareness of the process and barriers in various settings.